Fast software encryption 19th International Workshop, FSE 2012, Washington, DC, USA, March 19-21, 2012. Revised selected papers - FSE (Workshop) (Lecture notes in computer science, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the 19th International Workshop on Fast Software Encryption, held in Washington, DC, USA, in March 2012. The 24 revised full papers presented together with 1 invited talk were carefully reviewed and selected from 89 initial submissions. The papers are organized in topical sections on block ciphers, differential cryptanalysis, hash functions, modes of operation, new tools for cryptanalysis, new designs and Keccak. Block ciphers -- Differential cryptanalysis -- Hash functions -- Modes of operation -- New tools for cryptanalysis -- New designs -- Keccak.